2018
DOI: 10.1016/j.bbalip.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Maternal n-3 PUFA supplementation promotes fetal brown adipose tissue development through epigenetic modifications in C57BL/6 mice

Abstract: Brown adipose tissue (BAT) is a crucial regulator of energy expenditure. Emerging evidence suggests that n-3 PUFA potentiate brown adipogenesis in vitro. Since the pregnancy and lactation is a critical time for brown fat formation, we hypothesized that maternal supplementation of n-3 PUFA promotes BAT development in offspring. Female C57BL/6 mice were fed a diet containing n-3 PUFA (3%) derived from fish oil (FO), or an isocaloric diet devoid of n-3 PUFA (Cont) during pregnancy and lactation. Maternal n-3 PUFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 67 publications
(77 reference statements)
2
29
1
Order By: Relevance
“…Here, the decrease in placental and fetal lipid deposition by EPA supplementation may be attributable to the promotion of placental lipolysis while inhibiting lipogenesis, and increases in the expression of fatty acid transport genes and fatty acid oxidation. Previous studies have found that n‐3 PUFA promotes brown adipogenesis and adaptive thermogenesis via epigenetic modulation of PGC1α, UCP1, PRDM16, transcription in adipose tissues . Consistent with earlier reports, it was observed here that supplementation with EPA increased placental PGC1α and UCP1 expression and reduced HFD‐induced mitochondrial swelling, which may be of benefit for placental nutrient transport.…”
Section: Discussionsupporting
confidence: 92%
“…Here, the decrease in placental and fetal lipid deposition by EPA supplementation may be attributable to the promotion of placental lipolysis while inhibiting lipogenesis, and increases in the expression of fatty acid transport genes and fatty acid oxidation. Previous studies have found that n‐3 PUFA promotes brown adipogenesis and adaptive thermogenesis via epigenetic modulation of PGC1α, UCP1, PRDM16, transcription in adipose tissues . Consistent with earlier reports, it was observed here that supplementation with EPA increased placental PGC1α and UCP1 expression and reduced HFD‐induced mitochondrial swelling, which may be of benefit for placental nutrient transport.…”
Section: Discussionsupporting
confidence: 92%
“…To determine the FA profile in the BAT, the total lipids were extracted, as we previously described [15]. Briefly, approximately~100 mg of BAT was minced, and the extracted total lipids were converted into fatty acid methyl ester.…”
Section: Fatty Acid Profile Of Diet and Batmentioning
confidence: 99%
“…The BAT samples were fixed in 10% buffered formalin, embedded in paraffin, and cut into 5 µm sections. After deparaffinization, BAT sections were stained with hematoxylin and eosin (H&E) staining as previously described [15].…”
Section: Hande Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, environmental factors during development may influence the trajectory of BAT growth across the life course. For example, maternal diet during gestation and lactation and childhood cold exposure may alter BAT development and have consequences for energy expenditure in adulthood (Argentato, de Cássia César, Estadella, & Pisani, ; Fan, Toney, Jang, Ro, & Chung, ; Levy, ).…”
Section: Introduction: Why Measure Bat?mentioning
confidence: 99%